Literature findings on the phenomenon of foreign worker housing in peninsular Malaysia - Abd Shukor, Nur Nazirah; Mohd Amin, Suhaida (2023)
This article aims to highlight various research findings related to dependence and the negative effects of foreign workers in the Malaysian labour market. In addition, phenomenon related to their housing and accommodation will also be examined. This study uses the descriptive research method to investigate a phenomenon related to foreign workers. In this stage, the data collection process is based on examining reports, statistics, mass media and journals. Commentaries on the act and guidelines related to the housing and accommodation of foreign workers were also reviewed for understanding and reference of this study. It turns out that Malaysia is still dependent on foreign labour and the negative effects of the presence of foreign labour in Malaysia still occur. It is found that the management of foreign worker housing and accommodation in Malaysia is still not at a sustainable level. Existing policies still need to be improved in addition to non-compliance by employers on the guidelines provided. The research findings for this article are based on information from the literature highlights obtained from reports, journals, statistics, and the media. Therefore, no opinion polls were obtained from the policy maker, regulatory agency, and foreign workers themselves. A more in-depth study considering all parties is expected to give better implications for this kind of study. This literature finding is important to confirm the need for the next data collection process that will contribute a lot to knowledge, policymakers, and other stakeholders. Later, the completed research will be significant and important to the nation in providing decent housing and accommodation up to international standards and achieving the Sustainable Development Goals (SDG) set by the United Nations. This research is important as preliminary information before the actual data collection is done. The empirical study will be incomplete if the findings from the literature are not included.